PRODUK KERAJINAN BERBASIS KORAN BEKAS SEBAGAI UPAYA PEMBERDAYAAN IBU-IBU RUMAH TANGGA KELURAHAN TASIKMADU - prima vitasari; ST. Salammia; Sri Indriani; Anis Artiyani; Shinta Prastika; Priska Wulandari; Fatimah Az Zahro; Merina Ayu Ardini; Ina Anggraeni (JASTEN (Jurnal Aplikasi Sains Teknologi Nasional), 2021)
The increasing consumption of news and information that is widespread throughout the city has made used newspaper waste become abundant, due to the lack of attention from the public and the government. In fact, used newspaper waste can be processed into a product that has high economic value. The amount of paper or newspaper waste itself should be an opportunity to get extra income that can be obtained by local residents, one of which is a biocomposite material that can be used for handicraft products and other accessories. Efforts to empower the potential of housewives should be something that needs to be done, especially for those who depend on their family's economic income only on their husbands. As happened in Kelurahan Tasikmadu Malang, most of the housewives there have not even realized their potential. That reason is the background for the implementation of counseling on the use of newspaper biocomposite which aims to motivate and explore the potential of housewives in Kelurahan Tasikmadu Malang, especially in the neighborhood of RT 1 RW 4 Tasikmadu. With this training, it is hoped that mothers can gain knowledge and skills so that they can be applied in real life. The end result hopes that this activity can contribute to mothers to improve family welfare.